Retrospective Analysis of Demographic and Clinical Data in SARS-CoV-2 IgG Reactive Individuals Applied to Cerrahpasa Medical Faculty Hospital: 1 Year Evaluation - Akcin, Ruveyda; Ziver, Tevhide; Aydogan, Okan; Zurnaci, Fatma Ozlem; Ozbey, Dogukan; Dinc, Harika Oyku; Kocazeybek, Bekir Sami (Bilimsel Tip Yayinevi, 2023)
Introduction: SARS-CoV-2 IgG tests are used to determine whether an individual has had COVID-19 disease before, the antibody level resulting from vaccination, and the seroprevalence of COVID-19 in the community. Aim of this study was to evaluate the SARS-CoV-2 IgG levels, together with demographic and clinical data retrospectively from the cases who applied to the Serology/ELISA laboratory for suspected infection, history of the disease, or after vaccination. Materials and Methods: Cases that applied to our unit with a SARS-CoV-2 IgG test request between January 4, 2021 and December 31, 2021 and whose antibody test was found to be reactive were included in the study. Demographic and clinical data of the cases were obtained by retrospective examination. ELISA and CMIA based test kits were used for antibody detection. Results: The test was included 549 subjects with reactive SARS-CoV-2 IgG in the study. 308 (56.10%) were female, and 241 (43.90%) were male, with a mean age of 42.31 years. 159 (28.96%) of 549 cases were analyzed with ELISA and 390 (71.04%) with CMIA based test kit. In the period determined by the ELISA method, the antibody titer of the people who had the infection were higher than the antibody titer determined after the vaccination (p< 0.01), while the antibody titer of the people 61 years and older were found to be higher than the 18-50 age groups (p< 0.05). When the post-vaccination antibody test results were compared, there was no difference between the vaccine types, although there was a difference between the median values (p> 0.05). Conclusion: With the development of humoral and cellular immune response after COVID-19 infection, the antibody titers of people who had the infection during the study period with the ELISA method were found to be higher than after vaccination. Although there was no significant difference between the antibody titers against the vaccine types administered in different periods, it was determined that the antibody titers were higher after the reminder dose administration. We think that the application of the CoronaVac inactivated vaccine in this period and the vaccine causing a more humoral immune response may be related to the fact that the antibody levels of individuals aged 61 and over are higher than other age groups due to the priority of this age range in the vaccination process. We believe that large-scale studies should be conducted with kits suitable for standardization and give quantitative results to determine both seroprevalence and the immune response of the general population.
Keywords: SARS-CoV-2; ELISA; IgG; CMIA